2013
DOI: 10.1021/es4022156
|View full text |Cite
|
Sign up to set email alerts
|

Observations of Diurnal to Weekly Variations of Monoterpene-Dominated Fluxes of Volatile Organic Compounds from Mediterranean Forests: Implications for Regional Modeling

Abstract: The Estate of Castelporziano (Rome, Italy) hosts many ecosystems representative of Mediterranean vegetation, especially holm oak and pine forests and dune vegetation. In this work, basal emission factors (BEFs) of biogenic volatile organic compounds (BVOCs) obtained by Eddy Covariance in a field campaign using a proton transfer reaction−time-of-flight−mass spectrometer (PTR-TOF-MS) were compared to BEFs reported in previous studies that could not measure fluxes in real-time. Globally, broadleaf forests are dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 64 publications
3
33
0
Order By: Relevance
“…Unfortunately, to our best knowledge, no comparable studies exist in order to validate monoterpene emissions. For the Rome area, Italy, Fares et al (2013) concluded for a variety of typical Mediterranean tree and vegetation species mix, that MEGAN correctly simulated 10 mean observed monoterpene fluxes over the last two weeks of August 2007 within 10% error, as long as a canopy model was included (as in our study). meteorological parameters, the model can reproduce the daily concentration changes for these two species better than the hourly changes.…”
Section: Gaseous Speciessupporting
confidence: 70%
See 1 more Smart Citation
“…Unfortunately, to our best knowledge, no comparable studies exist in order to validate monoterpene emissions. For the Rome area, Italy, Fares et al (2013) concluded for a variety of typical Mediterranean tree and vegetation species mix, that MEGAN correctly simulated 10 mean observed monoterpene fluxes over the last two weeks of August 2007 within 10% error, as long as a canopy model was included (as in our study). meteorological parameters, the model can reproduce the daily concentration changes for these two species better than the hourly changes.…”
Section: Gaseous Speciessupporting
confidence: 70%
“…The local character of the comparisons for biogenic VOCs was pointed out, as well as the fact that biogenic OA is formed at a regional scale from these precursors rather than a 10 local scale. Available regional comparisons show acceptable comparisons for BVOC observed and simulated concentrations (Curci et al, 2010 ;Zare et al, 2012 ;Fares et al, 2013).Therefore, a systematic misrepresentation of BVOC in the model seem to be unlikely. For aerosol species, low bias was seen for BC, while an overestimation in simulations is observed for sulfates.…”
Section: Particulate Speciesmentioning
confidence: 99%
“…In total, 14 days of isoprene flux measurements were collected at this site. More detailed information on the experimental site and flux tower set up can be found in Fares et al (2013). Eddy covariance measurements were performed on the top of a self-standing tower 37 m above ground, using a Gill HS-100 sonic anemometer for the measurement of high frequency vertical wind velocities.…”
Section: Castelporziano Italy (Cp)mentioning
confidence: 99%
“…The undisturbed Mediterranean mixed oak forest of Castelporziano represented an excellent study site to test a new instrument in an environment rich in highly reactive volatile compounds. The data on VOC emission have been reported by Fares et al (2013a) and basal emission factors for isoprene and monoterpenes are reported in Table 1, with monoterpenes totaling 1,760 lg m -2 h -1 , approximately three times the emission of isoprene. High levels of ozone deposition to the forest canopy up to -5,530 lg m -2 h -1 (Fares et al 2013b) suggested that reactive compounds originated in situ from the Mediterranean vegetation, and other reactive compounds of anthropogenic origin transported through polluted urban plumes from the close urban area of Rome could contribute to ozone removal at canopy level.…”
Section: Measurements Of Isoprenoid Emissions In Castelporzianomentioning
confidence: 99%
“…In plant ecosystems, a direct method to measure ozone losses by isoprenoids is not yet available, but micrometeorological techniques allow to quantify stomatal and total ozone deposition, therefore calculating non-stomatal ozone deposition by difference between these two terms. Results from experimental measurements showed that in the central hours of the day, when light and temperature maximize isoprenoid emissions, non-stomatal ozone deposition can be larger than stomatal deposition (Kurpius and Goldstein 2003;Fares et al 2010Fares et al , 2012Fares et al , 2013aGerosa et al 2005).…”
mentioning
confidence: 99%